Mind the gap: translation in a fractured African society - Marion Arnold (2013)
The spaces and tensions between races, ethnic groups, and communities in late apartheid and post-1994 South African society, and the co-existence of different languages, religions and cultures, generated a society so fractured that cultural translation became a formidably difficult task. The concept of translation in a transforming society is examined through analysing two-dimensional language as a means of translating political events and experiences into visual forms, which attempt to communicate across cultural gaps. Iconic documentary photographs by Sam Nzima (1976) and TRC photographers (1997), struggle posters by cooperatives and formally trained designers, and artworks by Kevin Brand, Sue Williamson and Marion Arnold are discussed. The images reveal that different forms of visual representation encode different relationships of signifying content and aesthetic form to offer alternatives to speech and writing in communicating some implications of apartheid politics, leaving a legacy that validates art and design as tools of political activism.